Understanding the fishery dynamics and stock health of mahi-mahi Coryphaena hippurus (Linnaeus, 1758) from Indian coastal waters: Stock status of Mahi-mahi - E. M. Abdussamad; S. Surya; A. Margaret Muthu Rathinam; K. G. Mini; K. M. Rajesh; P. Abdul Azeez; T. B. Ratheesh; S. Febna; N. V. Dipti (Indian Journal of Fisheries, 2024)
This work delves into the mahi-mahi (dolphinfish) fishery along the Indian coast, noting its developmental stage precluding a full assessment. The analysis of population characteristics highlights their inherent resilience, driven by early maturity, substantial fecundity and rapid growth rates. These traits collectively mitigate susceptibility to fishing pressure, ensuring the maintenance of sizable spawning stock biomasses and recruitment. Through Kobe analysis, it is determined that the present fishing mortality and biomass levels remain within safe thresholds, indicating absence of overfishing. However, regular monitoring is imperative to swiftly implement management measures if necessary, safeguarding the sustainability of the mahi-mahi fishery in the long term. Keywords: Kobe plot, Population characteristics, Recruitment, Resilience, Spawning stock biomass